A new type of highly flame-retardant polyethylene-based shielding material
By adding modified nano-cerium oxide, lead powder, boron carbide and other ingredients into polyethylene-based nuclear radiation shielding materials, a new type of highly flame-retardant polyethylene-based shielding material was prepared, which solved the problem of existing materials being flammable under long-term radiation. problem, significantly improving shielding performance and flame retardant performance.
Patent Information
- Application Number
- CN202410132071.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-31
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-01-31
AI Technical Summary
Existing polyvinyl nuclear radiation shielding materials are prone to fire accidents under long-term radiation, and their flame retardant performance is insufficient, making it difficult to meet higher safety needs.
Ultra-high molecular weight polyethylene is used as the matrix, combined with modified nanometer cerium oxide, lead powder, boron carbide and dibenzoyl peroxide, and a new type of highly flame-retardant polyethylene-based shielding material is prepared through melt blending and granulation processes.
It significantly improves the shielding performance of the material on nuclear radiation, enhances flame retardant performance and mechanical performance, and ensures the safety and stability of the material in the radiation environment.
Smart Images

Figure BDA0004690104970000031 
Figure BDA0004690104970000032 
Figure BDA0004690104970000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nuclear radiation shielding materials, and in particular relates to a novel highly flame-retardant polyethylene-based shielding material. Background Art
[0002] Nuclear energy is a new type of energy. Compared with traditional energy, it has the advantages of being environmentally friendly, economical, and efficient. It has been rapidly developed in various fields such as military, medicine, industry, and life. This has also gradually increased the types and chances of people being exposed to nuclear radiation. Common radiation includes x-rays, gamma rays, and neutron radiation. These radiations not only endanger the safety and health of workers, but also affect the reliability and safety of equipment. Therefore, effective protection against nuclear radiation is necessary to ensure the safe use of nuclear energy in various fields.
[0003] Shielding materials can provide good protection against nuclear radiation. Shielding materials are mainly used to block and weaken gamma rays and neutron radiation that are harmful to the human body. They are an effective means to ensure the radiation safety of personnel, equipment and the environment.
[0004] Polyethylene (PE) has a high output, an ultra-high hydrogen content, and a good ability to weaken fast neutrons. Therefore, it is often used as a matrix and mixed with lead and boron to make shielding materials. Among them, boron can absorb thermal neutrons, and lead is particularly effective in shielding gamma rays. However, the oxygen index of polyethylene is relatively low, only about 17%, and it is a flammable material. Even if boron can absorb a certain amount of thermal energy, under long-term radiation, the radiant heat will accumulate inside it, which may cause PE molecular chain breakage, thermal degradation, and even combustion. In severe cases, it may lead to fire accidents and endanger human health and safety. Therefore, it is necessary to improve the flame retardancy of polyethylene to meet its higher demand in the field of nuclear radiation shielding materials. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a new type of highly flame-retardant polyethylene-based shielding material.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A novel highly flame-retardant polyethylene-based shielding material is prepared by the following steps:
[0008] Ultra-high molecular weight polyethylene, modified nano-cerium oxide, lead powder, boron carbide and dibenzoyl peroxide (initiator) are stirred and mixed uniformly, added into a twin-screw extruder, melt-blended, extruded and granulated to obtain a novel high flame-retardant polyethylene-based shielding material.
[0009] Furthermore, the usage ratio of ultra-high molecular weight polyethylene, modified nano cerium oxide, lead powder, boron carbide and dibenzoyl peroxide is 45g:16-20g:60g:5g:0.05g.
[0010] Ultra-high molecular weight polyethylene is used as the matrix, which has better radiation resistance and mechanical properties than ordinary polyethylene; the addition of lead powder and boron carbide greatly improves the matrix's shielding performance against nuclear radiation.
[0011] Further, the modified nano cerium oxide is prepared by the following steps:
[0012] S1. At room temperature, under nitrogen protection, in a three-necked flask equipped with a stirring device, tripolyphosphazene chloride, triethylamine and toluene were mixed, stirred until the solid was completely dissolved, 4-aminostyrene was added, the reaction temperature was controlled to 90°C, refluxed for 8 hours, the reaction was completed, filtered, part of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / chloroform, the volume ratio of the two was 6:3), the eluent was removed by rotary evaporation, and dried to obtain intermediate 1; the ratio of tripolyphosphazene chloride, triethylamine, toluene and 4-aminostyrene was 36.2g:30mL:150mL:77.8g;
[0013] Tripolyphosphazene chloride and 4-aminostyrene undergo nucleophilic substitution, and the molar ratio of the two is controlled to be close to 1:6 and 4-aminostyrene is slightly excessive, and triethylamine removes the hydrogen chloride generated by the reaction to obtain intermediate 1; the specific reaction process is as follows:
[0014]
[0015] S2. A three-necked flask equipped with a stirring reflux device was filled with nitrogen, and the intermediate 1, thioglycolic acid, AIBN (azobisisobutyronitrile) and acetonitrile were stirred and mixed uniformly, and refluxed at 75° C. for 4 h. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / chloroform in a volume ratio of 7:2), the eluent was removed by rotary evaporation, and dried to obtain intermediate 2; the ratio of the amount of intermediate 1, thioglycolic acid, AIBN, and acetonitrile was 85.2 g:9.1 g:1 g:150 mL;
[0016] Under the action of azobisisobutyronitrile, the unsaturated carbon-carbon double bond on intermediate 1 undergoes a thiol-ene click reaction with thioglycolic acid. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of intermediate 1, only one double bond on intermediate 1 participates in the reaction to obtain intermediate 2. The reaction process is as follows:
[0017]
[0018] S3, add intermediate 2 and acetonitrile to a three-necked flask equipped with a stirring device, heat to 45 ° C and stir continuously until intermediate 2 is completely dissolved; introduce nitrogen, add γ-aminopropyltriethoxysilane (silane coupling agent KH-550) and DCC (dicyclohexylcarbodiimide, dehydrating agent) and mix and stir evenly, heat to 60 ° C, keep warm for 50 minutes, filter after the reaction, remove the solvent by reduced pressure distillation, and vacuum dry to obtain intermediate 3; the ratio of intermediate 2, acetonitrile, γ-aminopropyltriethoxysilane, and DCC is 95.5g:175mL:22.1g:20.6g;
[0019] The carboxyl group of intermediate 2 and the amino group of γ-aminopropyltriethoxysilane undergo an amidation reaction. With the help of a dehydrating agent, the reaction can be carried out under mild conditions to obtain intermediate 3. The specific reaction process is as follows:
[0020]
[0021] S4, add intermediate 3 to a three-necked flask, ultrasonically treat for 10 minutes, add glacial acetic acid aqueous solution (mass fraction 5%), heat to 40°C until intermediate 3 is completely hydrolyzed, add nano cerium oxide, ultrasonically disperse evenly, reflux and stir at 85°C for 6 hours, add ammonia water dropwise, continue to reflux and stir for 8 hours, the reaction is complete, centrifuge and filter, wash the precipitate three times with deionized water, and dry to obtain modified nano cerium oxide; the ratio of intermediate 3, glacial acetic acid aqueous solution, nano cerium oxide, and ammonia water is 5g:50mL:1g:3mL;
[0022] There are many -OH groups on the surface of nano-cerium oxide, which react with the hydrolyzed intermediate 3 to obtain modified nano-cerium oxide;
[0023] There are a large number of oxygen vacancies in the structure of nano-cerium oxide, which can be used to fix the free oxygen produced by the degradation of organic matter under gamma-ray radiation conditions, and enhance the radiation resistance and thermal oxidation resistance of the matrix; and, through the chemical bonding action of grafting organic molecules, the interfacial compatibility of nano-cerium oxide and ultra-high molecular weight polyethylene can be greatly improved, and the agglomeration of nano-cerium oxide can be improved, thereby promoting the uniform dispersion of nano-cerium oxide and better performance; from the structure of the organic molecule itself, it belongs to the phosphazene flame retardant, which is low in smoke, non-toxic and halogen-free, and can give the matrix certain flame retardant properties; not only that, the PN flame retardant component in the organic molecule is an excellent halogen-free flame retardant component, which has the synergistic flame retardant effect of phosphorus and nitrogen flame retardants. It can give the matrix environmentally friendly and efficient flame retardant properties; in addition, silicon compounds can migrate to the surface of high molecular polymers at high temperatures to form a protective silicon dioxide layer; further enhancing the flame retardant properties of the matrix; in addition, organic molecules contain a large number of benzene rings, which can reduce the surface energy of the matrix, improve its corrosion resistance, and also improve certain mechanical properties; finally, the dendritic carbon-carbon double bonds in the organic molecules can produce chemical bonds with the polyethylene matrix under the action of trace initiators to play a cross-linking role and promote the formation of a cross-linked structure in the material, which can not only further enhance the interaction between the modified nano-cerium oxide and the matrix, but also the cross-linked network structure can further improve the mechanical properties of the shielding material;
[0024] It should be added that the heat resistance of ultra-high molecular weight polyethylene is poor, and modified nano-cerium oxide can improve the heat resistance of the matrix and make up for its defects.
[0025] Beneficial effects of the present invention:
[0026] 1. The shielding material prepared by the present invention uses ultra-high molecular weight polyethylene as a matrix, which has better radiation resistance and mechanical properties than ordinary polyethylene.
[0027] 2. The addition of lead powder and boron carbide greatly improves the shielding performance of the matrix against nuclear radiation.
[0028] 3. By grafting organic molecules with nano-cerium oxide, the interface effect and agglomeration phenomenon are significantly improved compared with ordinary nano-cerium oxide; the three elements P, N, and Si in the organic molecules can play a synergistic flame retardant role, significantly enhancing the flame retardant properties of the shielding material, and the performance is stable.
[0029] Therefore, the prepared shielding material has strong radiation resistance, high mechanical properties, stable and efficient flame retardancy, is halogen-free and environmentally friendly, and has important application value in the field of nuclear radiation shielding material technology. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] Preparation of modified nano-cerium oxide:
[0033] S1. At room temperature, under nitrogen protection, 36.2 g of tripolyphosphazene chloride, 30 mL of triethylamine and 150 mL of toluene were mixed in a three-necked flask equipped with a stirring device, and stirred until the solid was completely dissolved. 77.8 g of 4-aminostyrene was added, and the reaction temperature was controlled to 90° C., and the reaction was refluxed for 8 h. After the reaction was completed, the mixture was filtered, and part of the solvent was removed by rotary evaporation. The mixture was then purified by column chromatography (the eluent was a mixed solvent of benzene / chloroform, and the volume ratio of the two was 6:3), the eluent was removed by rotary evaporation, and the mixture was dried to obtain intermediate 1.
[0034] S2. A three-necked flask equipped with a stirring reflux device was filled with nitrogen, and 85.2 g of intermediate 1, 9.1 g of thioglycolic acid, 1 g of AIBN and 150 mL of acetonitrile were stirred and mixed evenly, and refluxed at 75° C. for 4 h. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / chloroform, and the volume ratio of the two was 7:2), the eluent was removed by rotary evaporation, and dried to obtain intermediate 2;
[0035] S3, add 95.5g of intermediate 2 and 175mL of acetonitrile to a three-necked flask equipped with a stirring device, heat to 45°C and stir continuously until intermediate 2 is completely dissolved; introduce nitrogen, add 22.1g of γ-aminopropyltriethoxysilane and 20.6g of DCC, mix and stir evenly, heat to 60°C, keep warm and react for 50min, filter after the reaction, remove the solvent by distillation under reduced pressure, and dry in vacuo to obtain intermediate 3;
[0036] S4. Add 5 g of intermediate 3 to a three-necked flask, ultrasonically treat for 10 min, then add 50 mL of glacial acetic acid aqueous solution (mass fraction 5%), heat to 40°C until intermediate 3 is completely hydrolyzed, add 1 g of nano-cerium oxide, ultrasonically disperse evenly, reflux and stir at 85°C for 6 h, then add 3 mL of ammonia water dropwise, continue reflux and stir for 8 h, the reaction is complete, centrifuge and filter, wash the precipitate three times with deionized water, and dry to obtain modified nano-cerium oxide.
[0037] Example 2
[0038] Preparation of modified nano-cerium oxide:
[0039] S1. At room temperature, under nitrogen protection, 72.4 g of tripolyphosphazene chloride, 60 mL of triethylamine and 300 mL of toluene were mixed in a three-necked flask equipped with a stirring device, and stirred until the solid was completely dissolved. 155.6 g of 4-aminostyrene was added, and the reaction temperature was controlled to 90° C., and the reaction was refluxed for 8 h. After the reaction was completed, the mixture was filtered, and part of the solvent was removed by rotary evaporation. The mixture was then purified by column chromatography (the eluent was a mixed solvent of benzene / chloroform, and the volume ratio of the two was 6:3), the eluent was removed by rotary evaporation, and the mixture was dried to obtain intermediate 1.
[0040] S2. A three-necked flask equipped with a stirring reflux device was filled with nitrogen, and 170.4 g of intermediate 1, 18.2 g of thioglycolic acid, 2 g of AIBN and 300 mL of acetonitrile were stirred and mixed uniformly, and refluxed at 75° C. for 4 h. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / chloroform, and the volume ratio of the two was 7:2), the eluent was removed by rotary evaporation, and dried to obtain intermediate 2;
[0041] S3, add 191.0g of intermediate 2 and 350mL of acetonitrile to a three-necked flask equipped with a stirring device, heat to 45°C and stir continuously until intermediate 2 is completely dissolved; introduce nitrogen, add 44.2g of γ-aminopropyltriethoxysilane and 41.2g of DCC, mix and stir evenly, heat to 60°C, keep warm and react for 50min, filter after the reaction, remove the solvent by distillation under reduced pressure, and dry in vacuo to obtain intermediate 3;
[0042] S4. Add 10 g of intermediate 3 to a three-necked flask, ultrasonically treat for 10 min, then add 100 mL of glacial acetic acid aqueous solution (mass fraction 5%), heat to 40°C until intermediate 3 is completely hydrolyzed, add 2 g of nano-cerium oxide, ultrasonically disperse evenly, reflux and stir at 85°C for 6 h, then add 6 mL of ammonia water dropwise, continue reflux and stir for 8 h, the reaction is complete, centrifuge and filter, wash the precipitate three times with deionized water, and dry to obtain modified nano-cerium oxide.
[0043] Example 3
[0044] 45g of ultra-high molecular weight polyethylene, 16g of modified nano-cerium oxide obtained in Example 1, 60g of lead powder, 5g of boron carbide and 0.05g of dibenzoyl peroxide were stirred and mixed evenly, added into a twin-screw extruder, melt blended, extruded and granulated to obtain a novel highly flame-retardant polyethylene-based shielding material.
[0045] Example 4
[0046] 45g of ultra-high molecular weight polyethylene, 18g of modified nano-cerium oxide obtained in Example 2, 60g of lead powder, 5g of boron carbide and 0.05g of dibenzoyl peroxide were stirred and mixed uniformly, added into a twin-screw extruder, melt blended, extruded and granulated to obtain a novel highly flame-retardant polyethylene-based shielding material.
[0047] Example 5
[0048] 45g of ultra-high molecular weight polyethylene, 20g of modified nano-cerium oxide obtained in Example 2, 60g of lead powder, 5g of boron carbide and 0.05g of dibenzoyl peroxide were stirred and mixed evenly, added into a twin-screw extruder, melt blended, extruded and granulated to obtain a new high flame retardant polyethylene-based shielding material.
[0049] Comparative Example 1
[0050] The difference from Example 5 is that common nano-cerium oxide with the same mass as the modified nano-cerium oxide is used.
[0051] Comparative Example 2
[0052] A commercially available lead-boron polyethylene material produced by Shandong Inwell New Materials Co., Ltd. was used.
[0053] Examples 3-5 and comparative examples 1-2 were made into corresponding shapes according to different test standards, and the following performance tests were performed:
[0054] The tensile strength is determined using the national standard GB / T 1040.2-2022 "Determination of tensile properties of plastics";
[0055] The notched impact strength is tested according to the national standard GB / T 1043.1-2008 "Determination of impact properties of simply supported beams of plastics";
[0056] The oxygen index is determined using the national standard GB / T 2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method";
[0057] The national standard GB / T 19466.6-2009 "Plastic Differential Scanning Calorimetry" was used to measure the induction time of the sample before and after hot air oxidation at 220°C for 48 hours.
[0058] The measured results are shown in Table 1:
[0059] Table 1
[0060]
[0061] The Cf-252 neutron radiation source is used, and a 12cm paraffin block is added to slow down the thermal neutron source. The imported neutron source from LND Company in the United States is used. 3The He proportional counter measures the thermal neutron attenuation coefficient of the sample;
[0062] Using Cf-252 neutron radiation source, 3 He counter measures the fast neutron attenuation coefficient;
[0063] use 60 CoY radiation source, using NaI crystal detector, to measure the sample γ radiation attenuation coefficient;
[0064] The measurement results are shown in Table 2:
[0065] Table 2
[0066]
[0067] It can be seen from the above two tables that the radiation resistance, mechanical properties, flame retardancy and heat resistance of the prepared shielding material are higher than those of commercially available shielding materials, and it has important application value in the field of nuclear radiation shielding material technology.
[0068] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0069] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A highly flame-retardant polyethylene-based shielding material, characterized in that: Prepared by the following steps: Ultra-high molecular weight polyethylene, modified nano-cerium oxide, lead powder, boron carbide and dibenzoyl peroxide are stirred and mixed uniformly, added into a twin-screw extruder, melt-blended, extruded, and granulated to obtain a highly flame-retardant polyethylene-based shielding material; Wherein, the modified nano cerium oxide is prepared by the following steps: S1. At room temperature, under nitrogen protection, tripolyphosphazene chloride, triethylamine and toluene were mixed and stirred in a three-necked flask, 4-aminostyrene was added, and the mixture was refluxed at 90° C. for 8 h, filtered, rotary evaporated, purified by column chromatography, rotary evaporated, and dried to obtain intermediate 1; the ratio of tripolyphosphazene chloride, triethylamine, toluene and 4-aminostyrene was 36.2 g:30 mL:150 mL:77.8 g; S2. A three-necked flask was filled with nitrogen, and intermediate 1, thioglycolic acid, AIBN and acetonitrile were stirred and mixed uniformly, and refluxed at 75° C. for 4 h, and rotary evaporated, purified by column chromatography, rotary evaporated, and dried to obtain intermediate 2; the ratio of intermediate 1, thioglycolic acid, AIBN, and acetonitrile was 85.2 g:9.1 g:1 g:150 mL; S3, add intermediate 2 and acetonitrile to a three-necked flask, heat to 45°C and stir continuously until intermediate 2 is completely dissolved; introduce nitrogen, add γ-aminopropyltriethoxysilane and DCC, mix and stir evenly, heat to 60°C, keep warm for 50 minutes, filter, distill under reduced pressure, and dry in vacuo to obtain intermediate 3; the ratio of intermediate 2, acetonitrile, γ-aminopropyltriethoxysilane, and DCC is 95.5g:175mL:22.1g:20.6g; S4. Add intermediate 3 to a three-necked flask, ultrasonically treat for 10 minutes, then add glacial acetic acid aqueous solution, heat to 40°C until intermediate 3 is completely hydrolyzed, add nano-cerium oxide, ultrasonically disperse, reflux with stirring at 85°C for 6 hours, add ammonia water dropwise, reflux with stirring for 8 hours, centrifuge and filter, wash the precipitate with deionized water, and dry to obtain modified nano-cerium oxide; the dosage ratio of intermediate 3, glacial acetic acid aqueous solution, nano-cerium oxide, and ammonia water is 5g:50mL:1g:3mL.
2. A highly flame-retardant polyethylene-based shielding material according to claim 1, characterized in that: The usage ratio of ultra-high molecular weight polyethylene, modified nano cerium oxide, lead powder, boron carbide and dibenzoyl peroxide is 45g:16-20g:60g:5g:0.05g.
Citation Information
Patent Citations
Overall lead-free X-ray shielding plastic compound material
CN101572129A
Preparation method of fatigue-resistant and irradiation-resistant diaphragm sizing material
CN108359181A